2010
DOI: 10.1017/s0950268810000385
|View full text |Cite
|
Sign up to set email alerts
|

Exact confidence limits for prevalence of a disease with an imperfect diagnostic test

Abstract: Estimation of prevalence of disease, including construction of confidence intervals, is essential in surveys for screening as well as in monitoring disease status. In most analyses of survey data it is implicitly assumed that the diagnostic test has a sensitivity and specificity of 100%. However, this assumption is invalid in most cases. Furthermore, asymptotic methods using the normal distribution as an approximation of the true sampling distribution may not preserve the desired nominal confidence level. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 24 publications
1
142
0
4
Order By: Relevance
“…vogeli antibodies (7) and clinical disease (27) . A study evaluating the mode of infection revealed that dogs with only indoor access have a lower frequency (P<0.05) of infection by E. canis (17) , most likely due to the close interaction with their owners. Such close interaction generates a greater zeal for ectoparasite control, and therefore lower parasitism of the dogs by the tick vector (5) .…”
Section: Resultsmentioning
confidence: 99%
“…vogeli antibodies (7) and clinical disease (27) . A study evaluating the mode of infection revealed that dogs with only indoor access have a lower frequency (P<0.05) of infection by E. canis (17) , most likely due to the close interaction with their owners. Such close interaction generates a greater zeal for ectoparasite control, and therefore lower parasitism of the dogs by the tick vector (5) .…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of real frequencies were made based on the sensitivity and specificity values of the auramine technique (sensitivity = 92.1%; specificity = 100%), as previously described by Chalmers et al (2011). The data were calculated based on the method described by Reiczigel et al (2010), using the EpiTools epidemiological calculators (SERGEANT, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The observed prevalence (OP) was calculated as the number of positive samples/total number of samples. The true prevalence (TP) was estimated using the following formula (Reiczigel et al 2010 Seroprevalence was analysed using the chi-squared and Fisher's exact tests, and a P-value of less than 0.05 was considered statistically significant. The 95% confidence interval for the adjusted prevalence of each estimate was calculated using Blaker's method (Reiczigel et al 2010).…”
Section: Methodsmentioning
confidence: 99%